Papers on Quintilian and ancient declamation - Winterbottom, Michael 1934- (Oxford University Press, 2019)
Declamation was central to the Greek and Roman educational systems over many centuries and the work of Michael Winterbottom has been seminal in the recent explosion of interest in the topic. This volume of his selected articles and reviews focuses on two related topics: the rhetorician Quintilian and ancient declamation in practice
Previously issued in print: 2019. - Includes bibliographical references and index
Keywords: Quintilian / Criticism and interpretation; Quintilianus, Marcus Fabius -- 35-100; Rhetoric, Ancient; Rhetorik